2015
DOI: 10.14254/2071-789x.2015/8-1/4
|View full text |Cite
|
Sign up to set email alerts
|

Personal characteristics of entrepreneurs in the context of perception and management of business risk in the SME segment

Abstract: Abstract. Th e issue of business in the segment of small and medium-sized companies is a very actual area of scientifi c research today. Currently, great importance is given to research of personal and knowledge preconditions of people for doing business. Th e aim of this article was to examine the relationship between personality characteristics and approach to the perception and management of business risks. Based on the preferred personality qualities and knowledge the entrepreneurs have been included into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 37 publications
(21 reference statements)
1
41
0
2
Order By: Relevance
“…Small and medium enterprises constitute the main focus in shaping business development policies in the European Union (EU) coming to the forefront of the world economy (Kozubikova et al, 2015;Ehrenberger et al, 2015;Dai et al, 2017;Durguner, 2017;Kotane & Kuzmina-Merlino, 2017;Kuhn et al, 2017;Strielkowski et al, 2017;Melnichuk, 2017;Viesi et al, 2017;Machová et al, 2016). According to many researchers, by 2020 more than 50% of all workplaces will be occupied by sole traders and freelancers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Small and medium enterprises constitute the main focus in shaping business development policies in the European Union (EU) coming to the forefront of the world economy (Kozubikova et al, 2015;Ehrenberger et al, 2015;Dai et al, 2017;Durguner, 2017;Kotane & Kuzmina-Merlino, 2017;Kuhn et al, 2017;Strielkowski et al, 2017;Melnichuk, 2017;Viesi et al, 2017;Machová et al, 2016). According to many researchers, by 2020 more than 50% of all workplaces will be occupied by sole traders and freelancers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Belás et al, 2015;Zapletalová et al, 2015). And Kozubíková et al (2015) also confirmed that small and medium-sized enterprises play an important role in the economic system of any developed country. Otherwise, approximately 25% of the respondents were classified as large.…”
Section: Fundamental Characteristics Of Respondentsmentioning
confidence: 58%
“…Th ey also fi nd that the market competition reduces the interest rates on the loan contract due to a tighter process of the loan. Jimenez et al (2009), Chakraborty & Hu (2006), Kozubíková et al (2015) also document a positive relationship between market competition and collateral requirements for small business lending.…”
Section: Literature Reviewmentioning
confidence: 87%